Cumprimento da sentença de obrigação de pagar quantia certa e a multa do artigo 475 “J” do Código de Processo Civil - Sousa, Ana Paula Nascimento dos Reis (2011)
This paper aims to demonstrate the changes generated in the process of implementing the reform legislation, specifically in regard to the fulfillment of the sentence required to pay a certain amount and a fine of Article 475 "J" Code of Civil Procedure. Will be focused on points such as the effectiveness of judicial protection, as well as accelerating the implementation process, and satisfaction of the creditor before the procedural syncretism